How do small businesses pursue sustainability? The role of collective agency for integrating planned and emergent strategy making. (14th May 2021) - Luederitz, Christopher; Caniglia, Guido; Colbert, Barry; Burch, Sarah
Abstract: Research on sustainability strategy in large corporations has shown that carefully planned strategies can address environmental and social concerns. However, we still lack clarity on how small businesses form sustainability strategies. Assuming that small businesses can—or should—carefully plan strategies is inappropriate considering that such organizations often lack the needed resources, foresight, and formalized decision‐making structures. Building on the study of two craft breweries in Canada and Germany, we detail how a combination of planned and emergent actions enables owners, employees, and external stakeholders to jointly form strategic sustainability orientation. Developing these findings into an integrated activity‐based model, we show the need to move beyond the dichotomy between planned and emergent strategizing. We contribute a human‐centered perspective to the sustainability strategy literature and suggest that research should take the role of people in small businesses more seriously as here interpersonal relationships and collective agency are central in forming strategic sustainability orientation.